A study on keyhole evolution and weld ripple formation in dissimilar welding under pulsed laser. (3rd October 2017) - Liang, Rong; Luo, Yu
ABSTRACT: A three-transient multiphase model is developed to study the dissimilar metal welding of pure niobium plate to titanium alloy Ti–6Al–4V sheet under pulsed laser. The physical process of dissimilar metal welding involves melting, resolidification, mass transfer, self-consistent keyhole, and weld bead formation. The major physical factors, such as recoil pressure induced by vapourisation, surface tension, heat transfer, fluid flow, Marangoni shear stress, buoyancy force, and their coupling are considered. The results show that the keyhole mainly occurs on the Ti–6Al–4V side due to the differences in physical properties of the materials. The effects of pulse overlapping factor on the weld bead are studied. It is found that the pulsed laser has a significant influence on the weld bead formation. The mixing of materials mostly occurred in the upper part of the molten pool. The simulated weld bead profile and the phase distribution agree well with the experimental results.